Short-Circuit Calculation in Distribution Networks with Distributed Induction Generators - Zhou, Niancheng (2016)
This paper presents an improved current source equivalent model method to determine the short-circuit current of a distribution system with multiple fixed-speed and variable-speed induction generators (IGs). The correlation coefficients of flux components between stator and rotor under the unsymmetrical fault are analyzed using the positive and negative sequence steady-state equivalent circuits of an IG. The terminal voltage and current responses of fixed-speed and variable-speed IGs with and without the rotor slip changes under different penetration levels are compared to investigate the coupling relation between the short-circuit currents of IGs and the nodal voltages in the distribution network. Then the transient equivalent potential of an IG at the grid fault instant is derived. Sequence components of the short-circuit current in the network can be determined using the proposed technique. The correctness of the proposed method is verified using dynamic simulation.